2020
DOI: 10.1136/heartjnl-2020-317650
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on percutaneous coronary intervention for ST-elevation myocardial infarction

Abstract: BackgroundThe objective of the study was to identify any changes in primary percutaneous coronary intervention (PCI) for ST-elevation myocardial infarction (STEMI) in England by analysing procedural numbers, clinical characteristics and patient outcomes during the COVID-19 pandemic.MethodsWe conducted a retrospective cohort study of patients who underwent PCI in England between January 2017 and April 2020 in the British Cardiovascular Intervention Society-National Institute of Cardiovascular Outcomes Research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
116
2
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(136 citation statements)
references
References 17 publications
15
116
2
3
Order By: Relevance
“…
Figure 4 Summary of reports in literature demonstrating the drop in STEMI volume and relative prevalence of COVID-19. 1 , 2 , 6 , 7 , 11 , 13 , 14 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 . For each country, the total number of COVID-19 cases, the cases per million, the drop in STEMI volume by percentages and the size of the study are shown.
…”
Section: Discussionmentioning
confidence: 99%
“…
Figure 4 Summary of reports in literature demonstrating the drop in STEMI volume and relative prevalence of COVID-19. 1 , 2 , 6 , 7 , 11 , 13 , 14 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 . For each country, the total number of COVID-19 cases, the cases per million, the drop in STEMI volume by percentages and the size of the study are shown.
…”
Section: Discussionmentioning
confidence: 99%
“…The “stay at home” messages given by the media could have led to an atmosphere of fear of contracting COVID-19 by leaving home and going to hospital. This is relevant for patients with cirrhosis that are at risk of severe COVID-19[ 5 , 6 ] and is in keeping with the delayed access to care observed for patients with stroke and myocardial infarction during the peak of COVID-19 outbreak in Spain and England[ 7 , 8 ]. Anyway, this is a speculation that has to be proven in well-designed studies.…”
Section: To the Editormentioning
confidence: 93%
“…Ovidio De Filippo , 1 Fabrizio D'Ascenzo , 2 Gaetano Maria Deferrari 1 'Time is muscle'. It has been almost 50 years since Professor Eugene Braunwald introduced the revolutionary hypothesis that the severity and the extent of myocardial injury resulting from coronary occlusion could be radically reduced by timely interventions.…”
Section: Covid-19 Pandemic and Infarctions: Another Call To Reorganismentioning
confidence: 99%
“…Such consideration is further supported by the increased 'door-to-balloon' time described by Kwok and collaborators. 2 The authors correctly point out that several factors may account Editorial for such delay, such as the necessity of a more extensive patient evaluation prior to angiogram and the time needed for the PCI staff to don personal protective equipment. However, while such explanations may look adequate in an unprecedented context as the global pandemic was, major efforts should be carried to prevent this from happening again.…”
Section: Covid-19 Pandemic and Infarctions: Another Call To Reorganismentioning
confidence: 99%